2020
DOI: 10.21037/atm-20-5965
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from skin precursor-derived Schwann cells promote axonal outgrowth and regeneration of motoneurons via Akt/mTOR/p70S6K pathway

Abstract: Background: Skin precursor-derived Schwann cells (SKP-SCs) have been shown to benefit the recovery of spinal cord injury (SCI) and peripheral nerve injury (PNI) with motor dysfunction. However, the effect of extracellular vesicles (EVs) from SKP-SCs responsible for neuroregeneration remains unknown.Methods: Based on the obtainment and identification of rat SKP-SCs and their derived EVs, the primary rat injury model of motoneurons resulting from axotomy in vitro or nerve crush in vivo, as well as the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…We previously confirmed that SKP-SC-EVs promote the axonal growth of the sciatic nerve [ 40 ]. A nerve graft constructed from SKP-SC-EVs can repair peripheral nerve defects [ 41 ].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…We previously confirmed that SKP-SC-EVs promote the axonal growth of the sciatic nerve [ 40 ]. A nerve graft constructed from SKP-SC-EVs can repair peripheral nerve defects [ 41 ].…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies have shown that SKP-SCs have an effect similar to that of primary SCs, such as the promotion of the functional recovery of nerve cells after treatment. SKP-SC-EVs have potential comparable to that of SKP-SCs and can significantly enhance the regeneration and recovery of damaged nerve cells [ 40 , 56 ]. In addition, we sequenced and analyzed SKP-SC-EVs in our previous study and found that they contained abundant miRNAs with antioxidant and anti-inflammatory effects, including miR-30a-5p, miR-22, miRNA-23a, and miR-27a/b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that SKP-SC-EVs could not only promote axonal regrowth and motoneuronal regeneration via the Akt/mTOR/p70S6K pathway but also improve the growth and survival of sensory neurons via the PTEN/PI3K/Akt axis. 23 , 24 …”
Section: Skin and Skin Derived Extracellular Vesiclesmentioning
confidence: 99%
“…Previous research showed that SKP-SC-EVs could not only promote axonal regrowth and motoneuronal regeneration via the Akt/mTOR/p70S6K pathway but also improve the growth and survival of sensory neurons via the PTEN/PI3K/Akt axis. 23,24 EVs can also be isolated from all body fluids, including blood, 25 breast milk, 26 urine, 27 saliva 28 and cerebral spinal fluid. 29 And viruses, bacteria, parasites and fungi release EVs in the process of infection.…”
mentioning
confidence: 99%